2013
DOI: 10.1155/2013/717459
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acid‐ and Ultraviolet/Ozonolysis‐Treated MWCNTs on the Electrical and Mechanical Properties of Epoxy Nanocomposites as Bipolar Plate Applications

Abstract: Carbon nanotubes (CNTs) have a huge potential as conductive fillers in conductive polymer composites (CPCs), particularly for bipolar plate applications. These composites are prepared using singlefiller and multifiller reinforced multiwalled carbon nanotubes (MWCNTs) that have undergone a chemical functionalization process. The electrical conductivity and mechanical properties of these composites are determined and compared between the different functionalization processes. The results show that UV/O3-treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…In addition, the attachment of functional groups on CNTs walls reduces electrical conductivity of the nanocomposites. Several authors reported observation of low composites conductivities because of acid treatment [23][24][25]. They ascribed this performance to the formation of functional groups and defects sites on the surface of the A-MWCNTs after modification process using acid treatment.…”
Section: Electrical Conductivity and Percolation Threshold Valuesmentioning
confidence: 99%
“…In addition, the attachment of functional groups on CNTs walls reduces electrical conductivity of the nanocomposites. Several authors reported observation of low composites conductivities because of acid treatment [23][24][25]. They ascribed this performance to the formation of functional groups and defects sites on the surface of the A-MWCNTs after modification process using acid treatment.…”
Section: Electrical Conductivity and Percolation Threshold Valuesmentioning
confidence: 99%
“…This result indicates that instead of using harsh chemical treatments (like acid), UV/O 3 can be used to improve the stiffness of this composite foam by improving the interlocking of the fibre-matrix interface. Some other observations in the previous studies also prove the reliability of UV/O 3 as a surface treatment to enhance the filler-matrix adhesion of composite [26,27]. Moreover, this method is cheap and environmentally friendly.…”
Section: Cell Size Density and Morphology Of The Hr/rhdpe Composite mentioning
confidence: 72%
“…In the chamber, RH was exposed to 10 L/min ozone flow rate for 30 min. All parameters in this study were based on previous studies [26] designated from the United States Patent (Wydeven), Patent No: US 6,555,835 B1 [33]. Initially, the sample was placed in a conical flask, which had ozone gas input and output flow channels, and in a reaction chamber with UV lamps (254 nm).…”
Section: Surface Treatment Of Rh Fibrementioning
confidence: 99%
See 2 more Smart Citations